Tomography of the Earth by Geo-Neutrino Emission - Tavares, Leonardo Estêvão Schendes (2014)
Geo-neutrinos are electronic anti-neutrinos originated from the beta decay process of some few elements in the decay chains of $^Th$ and $^U$ present in Earth\'s interior. Recent experimental measurements of these particles have been generating great expectations towards a new way for investigating directly the interior of the planet. It is a new multidisciplinary area, which might in the near future bring considerable clues about Earth\'s thermal dynamics and formation processes. In this work, we construct an inferential model based on the multigrid priors method to deal, in a generic way, with the geo-neutrino source reconstruction problem. It is an inverse problem; given a region in space V and a finite and small number of measurements of the potential generated on the surface of V by some charge distribution $ho$, we try to infer $ho$. We present examples of applications and analysis of models in two and three dimensions and we also comment how other a priori information may be included. Furthermore, we indicate the steps for inferring the best locations for future detectors. The objective is to maximize the amount of information liable to be obtained from experimental measurements. We resort to an entropic method of inference which may be applied right after the results of the multigrid method are obtained.